Dampak Bimbingan Belajar Dalam Mengurangi Kecemasan Menghadapi Ujian Akhir: (Studi Deskriptif Pada Pondok Pesantren Daruzzahidin Aceh Besar) - Mursyidah Umamah; Syaiful Indra; Reza Muttaqin (Yayasan Madinah Al-Aziziyah, 2026)
Anxiety regarding final exams is a common challenge faced by *santri* (Islamic boarding school students) due to academic demands and a packed schedule of boarding school activities. This study aims to describe the implementation of a tutoring program, its benefits for student readiness for final exams, and the factors supporting or hindering its execution at the Daruzzahidin Islamic Boarding School in Aceh Besar. A descriptive qualitative approach with purposive sampling was employed. Data were gathered through observation, interviews, and documentation involving the head of the Islamic boarding school, one teacher, and five santri and were analyzed using the interactive model of Miles and Huberman. The results indicate that the tutoring program is implemented in a structured manner, incorporating material review, discussions, practice questions, and guidance tailored to the boarding school's schedule. The program helps students approach final exams with greater readiness, particularly by improving their understanding of previously difficult material, fostering the confidence to ask questions, and increasing their assurance when answering exam questions. These factors help alleviate concerns about failure and the fear of exams, thereby reducing the anxiety experienced by some students. The program's implementation is supported by the cooperation of the school administration, the commitment of the teachers, student motivation, and a conducive learning environment; conversely, obstacles include the heavy schedule of boarding school activities, student fatigue, and varying learning abilities. This study demonstrates that tutoring has the potential to serve as a form of academic support that enhances both the academic and psychological readiness of students for final exams.